Structures and Functional Properties of Amorphous Alloys. Issue 2 (16th November 2020) - Jiang, Hongyu; Shang, Tongtong; Xian, Haijie; Sun, Baoan; Zhang, Qinghua; Yu, Qian; Bai, Haiyang; Gu, Lin; Wang, Weihua
Abstract : Amorphous alloys have attracted great attention due to their distinctive properties derived from unique packing structures. Recently, significant advances have been achieved for the understanding of structural characteristics and functional applications of amorphous alloys. Herein, an overview of the state of art of structure studies, accounting for the characteristics of amorphous alloys, are presented, and recent progresses in the functional applications of amorphous alloys are highlighted. The various structural models for the short‐range order, medium‐range order, and long‐range topological order for amorphous alloys are introduced. The functional applications in electrochemistry, mechanism, magnetism, optics, and biomedical engineering are presented in detail. The fundamental understanding of the correlations between structures and properties in amorphous alloys is discussed. Abstract : The major structural models and the recent functional applications of amorphous alloys are introduced herein. These structural models relate well with the atomic arrangements and the structure characteristics of amorphous alloys. The unique disordered structure endows amorphous alloys distinctive and outstanding properties which are not available in crystalline materials.